2019
DOI: 10.1007/s12040-019-1148-z
|View full text |Cite
|
Sign up to set email alerts
|

ENSO-induced groundwater changes in India derived from GRACE and GLDAS

Abstract: This study aims to quantify the interannual variations of groundwater storage changes (GWSCs) over India. GWSCs are derived from the gravity recovery and climate experiment (GRACE) and global land data assimilation system (GLDAS)-Noah life safety model (LSM) for the period 2003-2015. Estimated GWSCs are validated with the satellite altimetry over the six lake stations. The variability of GWSC and altimetry water-level heights are assessed with the cross-correlation and plotting analysis. Annual trends of GWSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 42 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The Menn-Kendall test (MKT) was employed to find a long-term trend in AOD over India. MKT is a non-parametric test widely used for analyzing trends in various research fields in time series or spatial variation of parameters (e.g., Asoka et al., 2017 ; Vissa et al., 2019 ). MKT takes the null hypothesis as no monotonic trend is present in a time series, and the trend values may be positive or negative.…”
Section: Methodsmentioning
confidence: 99%
“…The Menn-Kendall test (MKT) was employed to find a long-term trend in AOD over India. MKT is a non-parametric test widely used for analyzing trends in various research fields in time series or spatial variation of parameters (e.g., Asoka et al., 2017 ; Vissa et al., 2019 ). MKT takes the null hypothesis as no monotonic trend is present in a time series, and the trend values may be positive or negative.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown the influence of climate modes on GRACE and GRACE-FO measurements, but are usually restricted to regional (e.g. Becker et al 2011;Petrick et al 2014;Zhang et al 2015;Ndehedehe et al 2017;Vissa et al 2019;Xie et al 2019) or continental (e.g. de Linage et al 2013;Anyah et al 2018;Ndehedehe and Ferreira 2020;Liu et al 2020) scale studies, and/or to a limited subset of climate indices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Over the entire globe, Ni et al [46] examined the links between ENSO and GRACE TWS. Vissa et al [47] evaluated the relationship between ENSO-induced groundwater changes derived from GRACE and GLDAS over India. Liu et al [48] explored the role of teleconnections over TWS variations within the Asian and eastern European regions.…”
Section: Introductionmentioning
confidence: 99%